2005
DOI: 10.1590/s0100-39842005000600010
|View full text |Cite
|
Sign up to set email alerts
|

Auditoria em centro de diagnóstico mamário para detecção precoce de câncer de mama

Abstract: OBJETIVO: Este trabalho apresenta o modelo de auditoria nos resultados das mamografias do Centro de Diagnóstico Mamário da Santa Casa da Misericórdia do Rio de Janeiro. MATERIAIS E MÉTODOS: No período de maio de 1997 a setembro de 1998, foram realizadas 2.000 mamografias, sendo 1.570 em mulheres assintomáticas, cujos resultados foram objeto da auditoria. RESULTADOS: As mamografias das 1.570 mulheres assintomáticas foram classificadas em: categoria 1 - 1.362 casos; categoria 2 - 9 casos; categoria 3 - 95 casos;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
2
1
Order By: Relevance
“…In the present study, the PPV based on percutaneous biopsy (TP results/number of biopsies in categories 4 and 5) was 48.6%, superior to the expected range according to the literature (15% to 40%) ( 14 , 37 - 42 ) . Remarkably, category 3 presented a PPV of 1.3%, reproducing the values reported by Sickles et al ( 37 ) .…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…In the present study, the PPV based on percutaneous biopsy (TP results/number of biopsies in categories 4 and 5) was 48.6%, superior to the expected range according to the literature (15% to 40%) ( 14 , 37 - 42 ) . Remarkably, category 3 presented a PPV of 1.3%, reproducing the values reported by Sickles et al ( 37 ) .…”
Section: Discussioncontrasting
confidence: 77%
“…Such a result is superior to the one reported by Sickles et al ( 37 ) (93.1%) and by Baines et al ( 38 ) (69%), but reproduces the recommendations by Basset et al ( 14 ) (> 85%). The specificity observed in the present study was 97.4% and studies in the literature recommend results > 90% ( 14 , 37 , 38 , 42 ) . The authors attribute such results to the experience of the medical team (minimum 10-year training in breast imaging) and also to the quality of the mammography services provided by the center.…”
Section: Discussionsupporting
confidence: 63%
“…Taking these problems into consideration, the development of quality control programs represents a necessity in terms of efficiency, and an obligation in ethical and moral terms (3) . The imaging quality reduces, although does not eliminate, the occurrence of false-positive and falsenegative results.…”
Section: Introductionmentioning
confidence: 99%
“…Rosenberg et al [22] observed a PPV1 of 4.8% and a PPV2 of 24.6%. In a Brazilian study, Azevedo et al [23] reported a PPV1 of 11% and a PPV2 of 31%.…”
Section: Discussionmentioning
confidence: 95%